Creepy cat. 4 - Cotton Valent (Mangaka) (Seven Seas Entertainment, 2022)
"CREEP UP, CREEP OUT, CREEP...OVER?! Flora has vanquished her enemies and settled into life in a haunted mansion with the interdimensional Creepy Cat--but one day Creepy vanishes! Can Flora depend on Police Officer Oscar to find Creepy, or will the case of Oscar's own missing supernatural pets get in the way? Gloom is assured, and happiness not at all guaranteed in this final volume of Creepy Cat!"--Publisher.